2015
DOI: 10.1016/s2095-3119(14)60836-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial ability and growth promoting effects of feed supplemented with probiotic bacterium isolated from gut microflora of Cirrhinus mrigala

Abstract: The present studies were conducted to isolate, select, identify and characterize gut bacteria as antimicrobial and growth promoting agent for the feed of economically important fish Cirrhinusmrigala. Intestinal microflora were isolated, counted, and identified, and their in vitro antibacterial properties were determined. The results have revealed that occurrence of gram negative rods was around 75% and of gram positive rods was 25%. Amongst the isolates gram positive were maintained in nutrient agar slants at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The probiotic property of antagonism was confirmed by the results demonstrating the inhibitory effect against Aeromonas hydrophila. Here we observed a strong antibacterial activity of B. cereus strain SL1 showing the maximum inhibition (20 mm in diameter) against the pathogenic strain Aeromonas hydrophila, when performed by well diffusion assay which are not seen for wild-type strains (Bhatnagar and Lamba, 2015).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The probiotic property of antagonism was confirmed by the results demonstrating the inhibitory effect against Aeromonas hydrophila. Here we observed a strong antibacterial activity of B. cereus strain SL1 showing the maximum inhibition (20 mm in diameter) against the pathogenic strain Aeromonas hydrophila, when performed by well diffusion assay which are not seen for wild-type strains (Bhatnagar and Lamba, 2015).…”
Section: Resultsmentioning
confidence: 63%
“…The phylogenetic tree was plotted using Phylp 3.69 software and tree (phylogram) visualization was done by TreeViewX (Figure 2). Partial 16S rDNA gene sequence data analysis of strain CM2 showed high arrangements between traditional and molecular identification as established by traditional characterization earlier (Bhatnagar and Lamba, 2015), and the isolate was finally identified as Bacillus cereus strain SL1. However, distinguishing between toxic wild-type Bacillus cereus strains and this probiotic strain is crucial to assess the quality and possible hazard of feed.…”
Section: Resultsmentioning
confidence: 75%
“…The results of present study revealed that survival rates of fish were high in all the treatments between 73-90% for C. punctatus. Sarkar et al (2005) Bhatnagar and Lamba (2015) have also reported carcass protein in this range where experimental fish were fed on growth promoting diets clearly supporting that flesh quality of fish from rice cum fish culture has same nutritive value as in other intensive nutrition tests. The present study is also in accordance to the enhanced growth performance of C. carpio in paddy fields .…”
Section: Discussionmentioning
confidence: 76%
“…B.fusiformis also administered to L. vannamei daily or at intervals increased survival and prevented disease as immune system was boosted. [212]. On the other hand, B. subtilis increased Litopenaeus vannamei's antioxidant capacity and phenoloxidase activities [213].…”
Section: Enhancement Of Immune Response Resistance To Diseases In She...mentioning
confidence: 99%